PENGANGGURAN SEBAGAI PERHATIAN UTAMA EKONOMI MUHAMMADIYAH - Setiaji, Bambang (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2015)
Islamic teachings emphasize the reduction of unemployment in religious terminology is called the needy, the people who do not posses income. The indigent are entitled to charity or public funds from the government.Reduction of unemployment caused or inclusive of other economic targets such as the flow of revenue to the public and simultaneously reduce poverty, and reduce social problems. It is a concern of the Qur'an and is expressed in many verses. Alleviation of poverty in Islam, not based on charity, but based on the work (full employment).The complex problem of unemployment in this country should be a priority in religious movements, particularly Muhammadiyah. Because without getting a job and eventually dignity of one's faith itself would be problematic. It can directly reproduce the movement of employers or improve competence, quality, and skills of learners.